2008
DOI: 10.1097/wnr.0b013e3282fe2085
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pitch and pitch strength on an auditory-evoked N1m

Abstract: The aim of this paper was to determine whether the latency and/or amplitude of the N1m deflection of the auditory-evoked magnetic fields are influenced by the delay and number of iterations of iterated rippled noise, which are related to pitch and pitch strength, respectively. The results indicate that the N1m amplitude decreased sharply for delays between 16 and 32 ms, suggesting that the N1m amplitude reflects the lower limit of the audible pitch range. The N1m latency increases with increasing delay of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…vowel probes. The larger amplitude coupled with a more anterior source location in the periodic than in the aperiodic condition was similar to that found in several studies indicating cortical sensitivity to sound periodicity (Hertrich et al, 2000;Alku et al, 2001;Tiitinen et al, 2005;Lütkenhöner et al, 2006;Soeta and Nakagawa, 2008;Yrttiaho et al, 2008Yrttiaho et al, , 2009Yrttiaho et al, , 2010. This result might be taken to suggest that the population activated by the periodic stimulus is larger than that activated by the aperiodic stimulus and, thus, includes a distinct periodicity-sensitive subpopulation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…vowel probes. The larger amplitude coupled with a more anterior source location in the periodic than in the aperiodic condition was similar to that found in several studies indicating cortical sensitivity to sound periodicity (Hertrich et al, 2000;Alku et al, 2001;Tiitinen et al, 2005;Lütkenhöner et al, 2006;Soeta and Nakagawa, 2008;Yrttiaho et al, 2008Yrttiaho et al, , 2009Yrttiaho et al, , 2010. This result might be taken to suggest that the population activated by the periodic stimulus is larger than that activated by the aperiodic stimulus and, thus, includes a distinct periodicity-sensitive subpopulation.…”
Section: Discussionsupporting
confidence: 86%
“…The periodicity-specific adaptation and the periodicityspecific displacement in the N1m source location were, however, observed for both the 800 ms-and the 200-ms ISI. Several studies addressing the encoding of sound periodicity have found evidence for a specialized cortical population or populations responsive to sound periodicity (Griffiths et al, 1998(Griffiths et al, , 2001Hertrich et al, 2000;Alku et al, 2001;Patterson et al, 2002;Gutschalk et al, 2004;Penagos et al, 2004;Tiitinen et al, 2005;Soeta et al, 2005;Soeta and Nakagawa, 2008;Lütkenhöner et al, 2006;Hall et al, 2006;Hall and Plack, 2009;Yrttiaho et al, 2008Yrttiaho et al, , 2009Yrttiaho et al, , 2010Lewis et al, 2009;Schönwiesner and Zatorre, 2008;Griffiths et al, 2010). However, the few data sets that pertain to whether aperiodicity is also encoded by the activation of a specialized population do not seem to converge on the issue.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Auditory cortical sensitivity to sound periodicity has been previously observed in the amplitude or the source location ͑Martin and Boothroyd, 1999;Hertrich et al, 2000;Alku et al, 2001;Gutschalk et al, 2002Gutschalk et al, , 2004Gutschalk et al, , 2006Krumbholz et al, 2003;Soeta et al, 2005;Soeta and Nakagawa, 2008;Ritter et al, 2005;Tiitinen et al, 2005;Lütkenhöner et al, 2006;Yrttiaho et al, 2008 as well as in the latency ͑Krumbholz et Ritter et al, 2005;Soeta and Nakagawa, 2008͒ of event-related responses. In the current study, integration of speech periodicity was estimated by measuring the growth of the periodicity-sensitivity of the N1m response as a function of stimulus duration.…”
Section: Discussionmentioning
confidence: 94%
“…The most prominent transient event-related response of the human auditory cortex observable with MEG is the N1m, which peaks around 100 ms after sound onset and has an electroencephalographic ͑EEG͒ counterpart termed the N1 ͑Näätänen and Picton, 1987;May and Tiitinen, 2010͒. Previous research indicates that the N1m is sensitive to the periodicity of acoustic stimuli. This is evidenced by an amplification or anterior shift ͑Hertrich et Alku et al, 2001;Gutschalk et al, 2004Gutschalk et al, , 2006Soeta et al, 2005;Soeta and Nakagawa, 2008;Tiitinen et al, 2005;Lütken-höner et al, 2006;Yrttiaho et al, 2008 as well as by a͒ a decrease in the latency ͑Soeta and Nakagawa, 2008͒ of the N1m to periodic as opposed to aperiodic sound stimuli. Periodicity-sensitive transient cortical responses have also been observed to a change in the periodic structure of continuous auditory stimulation ͑Martin and Boothroyd, 1999; Krumbholz et al, 2003;Gutschalk et al, 2004;Ritter et al, 2005͒. With realistic speech stimuli, cortical sensitivity to vowel periodicity has been shown for stimulus durations of either 200 or 400 ms ͑Alku et al, 2001;Tiitinen et al, 2005;Yrttiaho et al, 2008 In continuous speech, however, the durations of periodic sounds are often shorter than this: short vowels and sonorants have average durations of 60-80 ms with ca.…”
Section: Introductionmentioning
confidence: 93%